THE NATURE OF TRUTH IN POST-TRUTH CONDITION - Fahmy Farid Purnama; Jesinta Moza Mustika (Dirosatuna: Journal of Islamic Studies, 2019)
Based on philosophical inquiries, this article attempts to inquiry and criticize the rise of relativism of truth in the post-truth condition and to reveal its relation with contemporary popular Islamic discourses in the public sphere. It cannot be denied that truth, both truth as a concept or as property, is an extremely basic concept and the philosopher’s value par excellence. Considering the extent of its scope, the inquiry of truth in philosophical discourse is often connected to the system of human belief, knowledge, concept of logic, language, and reality. The philosopher’s fascination in the discourse of truth could be deduced by three problems: how the truth acquired, the relation of truth to linguistic meaning, and the relation between truth and logic. In ancient philosophy, the idea of truth broadly refers to physical or natural order as truth’s ontological sine qua non. Different from classical philosophy, the truth in the realm of modern philosophy refers to the critical and self-reflective subjectivity of the subject that seeks objective truth. While the key terms that illustrate the conditions of contemporary philosophical discourse are postmodernism which is characterized by the mistrust of the grand narratives. In contemporary age—the age of disruption which technology forms and accelerates human life and also driven by the mistrust of the grand narratives campaigned by postmodernism philosophical thought, the nature of truth undergoes some radical change. The symptom of radical changes that occur in truth value lies in the problem that feeling or believing something matter more than fact in shaping public opinion. At the level of academic discourses, the current situation is often expressed as the post-truth condition which is often characterized by the disappearance of objective truth—the prefix “post” does not refer to the temporal sense, but in the sense that truth has been eclipsed. In the post-truth condition, which relativism of truth is often at its peak, philosophical discourses, including Islamic philosophy, find its challenges. By inquiring about the nature of truth through ontological, epistemological, axiological, and semantical inquiries, this article seeks to a better understanding of the dynamics of philosophy in the post-truth condition and try to critically analyze and search for solutions to avoid the eclipsed truth based on the philosophical lens.